Physical Properties of Briquette Fertilizers Made from Urea and Fly Ash-Azolla - Agus Hermawan; Adipati Napoleon; Bakri Bakri (JOURNAL OF TROPICAL SOILS, 2018)
Coal fly ash and Azolla biomass are potential materials to be used as raw materials for the manufacture of briquette fertilizers. In this study, the coal fly ash, azolla and urea in various compositions were mixtured to make briquette fertilizers. The study was conducted to evaluate the physical properties of briquette fertilizers, i.e bulk density, compressive strength, porosity, and water holding capacity on various compositions of fly ash-azolla and urea. The research was arranged in a Completely Randomized Design with three replicates. The formulation of briquette fertilizers as treatments was made with the compossition (w/w, dry-weight basis) of (fly ash : azolla) + urea as follows: (40:60)90+10; (40:60)80+20; (40:60)70+30; (50:50)90+10; (50:50)80+20; (50:50)70+30; (60:40)90+10; (60:40)80+20 and (60:40)70+30. The results showed that the variation in composition of coal fly ash-azolla and urea significantly affected the compressive strength, bulk density, water holding capacity and porosity of briquette fertilizers produced. The increase in the proportion of fly ash or the decrease of azolla biomass proportion tends to increase compressive strength and bulk density, and tends to decrease the water holding capacity and porosity of briquette fertilizers produced.